Modeling Of Subscriber Station Energy Consumption Network 802.16 - M. Yudha Al Hakim (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2021)
Worldwide Interoperability for Microwave Access (WiMAX) is a Broadband Wireless Access (BWA) technology that has high speed and wide access for multimedia communication. The reception of quality video or voice packets at the receiver is related to how efficient the energy consumption is sent by the Subscriber Station (SS). The more video or voice packets that are sent, the more energy consumption is needed. One way to calculate energy consumption at a WiMAX subscriber station is by using mathematical modeling. This final project is modeling energy consumption in WiMAX. From the simulation, it is found that the change in the bit rate affects the energy consumption of the subscriber station. Through simulation, training data is generated to obtain a mathematical model.The mathematical model contains the components of the state duration and the level of energy consumption. Mathematical models are then used to predict energy consumption in WiMAX. The model is tested through the generation of test data. The test results through simulation showthe percentage deviation of the average energy consumption of training data with mathematical modeling on average is 0.180%. Meanwhile, the energy consumption of test data and mathematical models has an average deviation of 0.187% and 0.191%. The least energy consumption is generated when the MAC Initialization state (state i0) is 0.001 Joule, while the highest energy consumption is the Uplink Frame state (state i14) of 101.017226 Joule.